Child/youth, family and public engagement in paediatric services in high‐income countries: A systematic scoping review. (24th January 2020) - Gurung, Gagan; Richardson, Amy; Wyeth, Emma; Edmonds, Liza; Derrett, Sarah
Abstract: Background: Patient and public engagement in paediatric health‐care decision making is under‐researched, and there is a lack of systematically reviewed literature in this area. Objective: To examine the extent, range and nature of published research investigating the engagement of children/youth, families and the public in paediatric service improvement, to summarize key aspects of the research identified and to identify gaps to help inform future research needs. Methods: Literature was sought in MEDLINE, EMBASE, PsycINFO and CINAHL. Eligible articles presented research focused on patient, family and public engagement strategies in the paediatric health‐care setting. Two reviewers extracted and charted data and analysed findings using a descriptive numerical summary analysis and a thematic analysis. Results: From 4331 articles, 21 were eligible. Most were from the United States. The majority of studies were undertaken in hospital settings and used quantitative methods. Various patient and public engagement strategies/interventions were examined, including shared decision‐making tools, questionnaires, youth councils/family advisory groups, patient portals and online networks. Most of the studies examined child/youth/parent satisfaction, with fewer investigating treatment outcomes or service improvement. The majority of studies investigated an engagement strategy at the 'individual treatment' level of engagement. Regarding the continuum of engagement, most of the studies were at either the 'consultation' or 'involvement' stage. Conclusion: Future research needs to focus on the investigation of engagement strategies delivered in primary care, and the use of more qualitative and mixed methods approaches is recommended. There is a gap in the area of engagement strategies directed towards 'service design and resources' and 'macro/policy' levels.